Ekranisasi Novel Winter In Tokyo Karya Ilana Tan dalam Bentuk Film Winter In Tokyo Karya Fajar Bustomi - Khasanah, Zulia Munna; Awaliyah, Sindi; Sajida, Yasmine Adzka; Damanik, Zeinny Permatasari Syaputri; Syahrani, Natasya Fiqih; Yuniawan, Tommi; Neina, Qurrota Ayu (UPA Bahasa Universitas Tidar And HISKI Kedu, 2024)
This research aims to explore the ecranization of the novel